The Influence of diet on the course and activity of Crohn's disease and ulcerative colitis - a review of available literature - Dębińska, Julia; Bentkowska, Zuzanna; Golemo, Jagna; Szpyra, Justyna; Kałuża, Izabela; Górska, Magdalena; Dziuba, Gabriela; Bogoń, Aleksandra; Ostojska, Magdalena; Miazga, Małgorzata (Quality in Sport, 2024)
Introduction: Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the digestive tract. It is a clinical entity that includes: Crohn's disease (CD) and ulcerative colitis (UC). Food intake is an important environmental factor that influences the development of IBD. This article reviews studies on different dietary options and their effects on the course and activity of Crohn's disease and ulcerative colitis. Materials and methods: A review of the literature available in the PubMed database was carried out, using the key words: ”inflammatory bowel disease”; ”Crohn disease”; ”diet”; “nutrition”; „colitis ulcerosa”. Results: Appropriate diet selection is important in the course of inflammation in the intestines. It influences disease activity. It turns out that the diet improves inflammation parameters, clinical symptoms, and quality of life. In patients with inflammatory bowel disease, one should also remember about deficiencies such as iron, vitamin D or protein deficiency, the demand of which is increased in sick patients compared to the general population. Conclusions: An individualized approach to nutritional therapy may be one of the main branches of treatment for patients with inflammatory bowel diseases. However, there is a need for further research on larger groups of patients in order to effectively implement it into treatment standards.